América Latina, s. XVII-XXI. Una aproximación hacia la historia de los cuerpos y el ejercicio de las violencias - María José Correa Gómez; Romané Landaeta Sepúlveda (Nuevo mundo - Mundos Nuevos, 2009)
This introduction presents a set of questions related to the bodies and the application of violence. We understand bodies as plural and meaningful platforms and violence from three interrelated perspectives: collective violence, normative structures and individual conflicts. Acknowledging the complex relationship between these two concepts this introduction invites to study their historical articulation in the context of Latin America and Spain between the 17th  and 21st centuries.